Results‐based management of wicked problems? Indicators and comparative evidence from Latin America. (15th April 2022) - Kirschke, Sabrina; Avellán, Tamara; Benavides, Lucía; Caucci, Serena; Hahn, Angela; Müller, Andrea; Rubio Giraldo, Claudia Beatriz
Abstract: Environmental problems are often wicked, shaped by conflicts, complexity, and uncertainty. Research is called here to design effective management approaches adapted to these specific features of environmental problems. However, management approaches hardly account for both result‐orientation and the respective management needs in the face of wicked problems. By combining the results‐based management literature with an analytic understanding of wickedness, we identify 12 indicators for an effective management along four management stages (inputs, activities, outputs, and outcomes) and three dimensions of wicked problems (goal diversity, system complexity, and uncertainty). An interview‐based demonstration of the concept in the Latin American context suggests a chain of effects regarding the stages, which differs slightly concerning dimensions of wicked problems. A lack of resources results here in limited activities, outputs, and outcomes to address problems, which is further substantiated by diverse challenges throughout the results‐chain. While these patterns are pertinent for all dimensions of wicked problems, we also find varying challenges for addressing conflicts, complexity, and uncertainty. These results call for more rigorous analysis at the policy capacity level and along the dimensions of wickedness as a starting point for achieving effective policies to address wicked environmental problems at the outcome level.